Compliance levels of profession student in self protection against radiation exposure: Tingkat kepatuhan mahasiswa profesi dalam proteksi diri terhadap paparan radiasi - Barunawaty Yunus; Asti Sanjiwai Tenriyara M. (Makassar Dental Journal PDGI Makassar, 2020)
Objective: This study aimed to determine the compliance levels of profession student in self protection against radiation exposure at Dental Radiology, Dental Hospital, Hasanuddin University. Methods: This observational descriptive with cross- sectional study design used 30 samples consisted of 14 samples using conventional periapical radiographic techniques, 9 samples using panoramic technique, and 7 samples using digital occlusal and periapical radiographic techniques, conducted anassessment ofprofessional students who performradiographic examinations based onquestionnaire about standard operating procedures (SOP) of radiographic examination. The study was conducted in March 2015. Result: sample distribution based conventional periapical radiography (46.7%), periapical and occlusal appliance digital radiography (23.3%), and panoramic radiography(30%). The compliance over view to the SOP using conventional periapical radiography as much as 61.1%, while 37.3% did not obey. The compliance overview to the SOP and the use of radiographic periapical digital occlusal as much as 69.8%, while 30.1% did not obey. The compliance overview to the SOP for using panoramic radiography as much as 64.8% while 35.1% did not obey. Conclusion: Level of self-protection in not optimal because there are still many students who do not follow the SOP which must be done before radiographic examination, especially the use of whole-body apron for the operator, the use of thyroid apron in the patient and turmolumenisence dosimetry for the operator.